2016
DOI: 10.1186/s12906-016-1230-x
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin inhibits excitatory amino acid agonist-and high-dose morphine-induced nociceptive behavior in mice via modulation of N-methyl-D-aspartate receptors

Abstract: BackgroundPain, the most common reasons for physician consultation, is a major symptom in many medical conditions that can significantly interfere with a person’s life quality and general functioning. Almost all painkillers have its untoward effects. Therefore, seeking for a safe medication for pain relieve is notable nowadays. Paeonia lactiflora is a well-known traditional Chinese medicine. Paeoniflorin is an active component found in Paeonia lactiflora, which has been reported to inhibit formalin-induced noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…But as NSAIDs often cause severe gastrointestinal adverse effects, it is necessary to find new analgesic drugs with minimal adverse effects. The research showed that PF had good anti-inflammatory and analgesic effects, especially when it was used in combination with morphine [26,27]. Nevertheless, the analgesic mechanism of PF is poorly understood yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But as NSAIDs often cause severe gastrointestinal adverse effects, it is necessary to find new analgesic drugs with minimal adverse effects. The research showed that PF had good anti-inflammatory and analgesic effects, especially when it was used in combination with morphine [26,27]. Nevertheless, the analgesic mechanism of PF is poorly understood yet.…”
Section: Discussionmentioning
confidence: 99%
“…PF can improve CNS diseases such as cognitive impairment, depression, and Parkinson's disease [21][22][23][24][25]. The combined use of PF and opioid analgesics could potentiate the analgesic effect of opioid analgesics in the treatment of cancerous pain as compared with the use of opioid analgesics alone [26,27]. Our previous study demonstrated that PF exerted the anti-inflammatory effect by inhibiting the activation of microglia [28].…”
Section: Introductionmentioning
confidence: 99%
“…Paeoniflorin attenuates neuropathic pain via MAP-kinase pathway [29]. It also mediates neuroprotective effect, hence ameliorating the function of cholinergic nerve [30][31][32]. Paeoniflorin also relieves oxidative stress and downregulates NF-κB expression, hence damping proinflammatory cytokine production [33].…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibited inflammatory pain via modulation of N‐methyl‐D‐aspartate in the brain cortex and reduced related cytokines, such as tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐1β, IL‐6, IL‐10, IL‐12, and IL‐17 (Dai et al, ; Sun et al, ; Xu et al, ). Paeoniflorin upregulated apoptosis of MGC‐803 human gastric carcinoma cells and HT29 human colorectal cancer cells (Chen, Lee, et al, ; Parker et al, ; Zheng et al, ). It inhibited proliferation, invasion, and metastasis of MCF‐7/MDA‐MB‐231 human breast cancer cells and human A549 lung cancer cells (Parker et al, ; Zhang, Yuan, Cui, Xiao, & Jiang, ; Zhou, Wang, Song, & Hu, ).…”
Section: Discussionmentioning
confidence: 99%